Location of the targeted lymph node in a mandibular lymphocentrum: A needle aspiration model in canine cadavers. (16th July 2021) - Bae, Sohee; Townsend, Katy L.; Milovancev, Milan
Abstract: Accurate tumour staging has a profound impact on the care and prognosis of oncologic patients. Due to the presence of multiple lymph nodes (LNs) in the mandibular lymphocentrum, clinicians may not know which specific LN they are sampling during routine fine needle aspirations, which introduces a source of uncertainty in accurately determining patient clinical stage. The objective of this cadaveric study was to determine the success of targeting specific mandibular LNs by palpation alone, verified by computed tomography (CT). A 1.5‐inch, 22‐gauge needle was inserted into the targeted LN (selected by drawing with the equal sample sizes of the left/right mandibular lymphocentrum and the lateral/medial node) and success was evaluated by CT images in transverse, sagittal and dorsal views. The overall success rate of inserting the needle into the targeted LN was 55.9%. One variable was significantly associated with successful needle insertion: lateral (vs. medial) LN location ( p  = .019). In addition, the distance from the LN to the ventral skin surface in the successful group appeared to be shorter compared to the unsuccessful group (3.37 mm [1.55–6.46] vs. 4.9 mm [1.57–17.79], p  = .066). These findings suggest that physical accessibility of the LN is the most important factor for successful needle insertion using palpation. Palpation‐based sampling of specific mandibular LNs is often inaccurate and if targeted sampling of a particular LN is required, additional methods should be used to guide accurate sample acquisition.